Exploring plasmonic coupling in hole-cap arrays - Schmidt, Thomas M.; Frederiksen, Maj; Bochenkov, Vladimir; Sutherland, Duncan S. (Beilstein Journal of Nanotechnology, 2015)
The plasmonic coupling between gold caps and holes in thin films was investigated experimentally and through finite-difference time-domain (FDTD) calculations. Sparse colloidal lithography combined with a novel thermal treatment was used to control the vertical spacing between caps and hole arrays and compared to separated arrays of holes or caps. Optical spectroscopy and FDTD simulations reveal strong coupling between the gold caps and both Bloch Wave-surface plasmon polariton (BW-SPP) modes and localized surface plasmon resonance (LSPR)-type resonances in hole arrays when they are in close proximity. The interesting and complex coupling between caps and hole arrays reveals the details of the field distribution for these simple to fabricate structures.
Keywords: caps; colloidal lithography; hybridization; localized surface plasmon resonance; near field; SRO hole arrays